Resource management for individuals and families - Goldsmith, Elizabeth B. (Thomson/Wadsworth, 2005)
Elizabeth B. Goldsmith (Ph.D., Michigan State University) is Professor of Resource Management and Consumer Economics at Florida State University where she has been the recipient of the University Teaching Award and the Teaching Incentive Award for teaching excellence. Dr. Goldsmith's published writings include journal articles, encyclopedia chapters, and a textbook, Resource Management for Individuals and Families, Second Edition. She has served as associate editor of the Journal of Family and Consumer Sciences, and as an advisor to the Wall Street Journal, the United Nations, and other organizations. Her research interests focus on work and family, women and money, the functioning of the American home, and environmental issues.